A NOVEL SCHIFF BASES/MULTIWALLED CARBON NANOTUBE BASED ADSORBENTS TO REMOVE ²¹⁰Pb FROM WATER - ASLAN, Nazife; ATAKOL, Orhan; ŞEN, Nilgün (Studia Universitatis Babeș-Bolyai Chemia, 2022)
This work presents the development of new adsorbent materials to remove lead-210 (210Pb) from water. Adsorbents were constructed from the carboxylated carbon nanotubes modified with N,N'bis(salicylidene)1,3-diaminopropane (LH2) Schiff Base and N,N'bis(salicylidene)1,3-diaminopropane-Cu(II) (CuL) complexes. Scanning electron microscopy (SEM) was used to characterize the morphological features of the adsorbents. The effects of pH, contact time, temperature, and Schiff base concentration on lead(II) absorption were investigated in order to optimize the experimental conditions. The adsorption capacity of the adsorbents was determined using atomic absorption spectrometry. Both adsorbents had high adsorption capabilities, with about 98.0% in the first 30 minutes of contact time. The adsorption processes were also in good agreement with the Langmuir isotherm and pseudo-second-order kinetic models. The adsorption of 210Pb from the tap water sample confirmed the applicability of the proposed adsorbents, and the results were satisfactory.